Determination of carbonate content in barite ore by headspace gas chromatography. Issue 1 (14th November 2022) - Liu, Xue‐Yan; Li, Wei; Yu, Kang; Fan, Zhi‐Yu; Luo, Bin; Nie, Deng‐Pan; Luo, Ying‐Chun; Dai, Yi; Wang, Hao
Abstract : This paper reports a method for determining the carbonate content in barite ore using headspace gas chromatography. Based on the acidification reaction, the carbonate in the barite ore was converted to CO2 in a closed headspace vial. When the carbonate content was significant, the pressure caused changes in the CO2 and O2 signals and affected the measurement accuracy. It was found that carbonate content is proportional to the intensity ratio of the CO2 to O2 signals. Thus, the carbonate content in barite ore can be measured indirectly using a theoretical model. The results showed that the carbonate in 3 g of barite ore sample with a particle size of 74 μm could react completely with a hydrochloric acid solution (2 mol/L) at 65°C for 5 min. The method described herein had good precision (relative standard deviation < 4.14%) and accuracy (relative differences < 6.12%). Further, the limit of quantification was 0.07 mol/L. Owing to its simplicity and speed, this method can be used for the batch determination of carbonate content in barite ore.